STUDENTSâ PERCEPTION ON LISTENING TO ENGLISH MONOLOGUE TEXT AT THE FIFTH SEMESTER OF ENGLISH STUDY PROGRAM OF UNISI TEMBILAHAN - Yeni, Melda (Islamic University of Indragiri, 2017)
This research was done because the researcher found that studentsâ perception in listening to English monologue text is being a question. Therefore, the researcher decided to conduct a research about it. Due to the fact that the researcher wants to find out studentsâ perception on listening to English Monologue text at the fifth semester of English Study Program of UNISI, This aim was achieved through descriptive qualitative design. The sample of this research was the students at the fifth semester of English Study Program of UNISI Tembilahan. They consist of 25 students. By conducting this, the researcher found that studentsâ perception on listening to English monologue text at the fifth semester of English Study Program of UNSI is categorized into less level. It can be interpreted that listening to monologue spoken text is difficult. Therefore, based on this result, the researcher assumed that the studentsâ low result is caused by their less perception of listening to monologue text.